ICTV Virus Taxonomy Profile: Geminiviridae 2021. (17th December 2021) - Fiallo-Olivé, Elvira; Lett, Jean-Michel; Martin, Darren P.; Roumagnac, Philippe; Varsani, Arvind; Zerbini, F. Murilo; Navas-Castillo, Jesús
Abstract : The family Geminiviridae includes viruses with mono- or bipartite single-stranded, circular DNA genomes of 2.5–5.2 kb. They cause economically important diseases in most tropical and subtropical regions of the world. Geminiviruses infect dicot and monocot plants and are transmitted by insect vectors. DNA satellites are associated with some geminiviruses. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Geminiviridae which is available at ictv.global/report/geminiviridae .